El Excentrico, 1952-03-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
March 20, 1952 [20 de marzo de 1952]. Ano 2, No. 10. Cover contains a photo of a young girl sitting next to her dog. The girl has a serious expression while the dog is panting happily. Both of them are looking at the viewer.